Strategi Lembaga Pengembangan Tilawatil Qur'an dalam Penguatan Literasi Bahasa Arab melalui Program Tahfidz Al-Qur'an - Haer, Jaenudin; Jaelani, Aan; Sudrajat, Anton (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to describe and analyze the strategy of the Qur'an Tilawatil Development Institute (LPTQ) in strengthening Arabic literacy through the Tahfidz Al-Qur'an program. This study uses a qualitative research type with a systematic literature review (SLR) approach. The research data are in the form of scientific documents including journal articles, research reports, and institutional documents related to LPTQ, tahfidz programs, and Arabic literacy. Data sources are drawn from Google Scholar, DOAJ, and the Garuda Portal databases, covering 2015–2025, in Indonesian and English, and derived from Sinta-accredited or DOAJ-indexed journals. Data collection was carried out using a systematic documentation study technique, following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow. The total 500 articles identified before screening, a systematic selection stage was carried out including the removal of duplicates, screening of titles and abstracts, and full-text feasibility testing, resulting in 10 articles that met all inclusion criteria and were used in the research synthesis. Data analysis used content analysis techniques combined with critical analysis, namely identifying main themes, codifying the data thematically, and then comparing the findings with language acquisition theories and relevant Islamic educational discourses. The results of the study indicate that LPTQ applies three main strategies: the talaqqi method, a structured ḥalaqah system, and an integrated curriculum based on memorization (tahfidz). This program has been proven to develop phonetic competence through makhārij al-ḥurūf, enrich understanding through the duplication of mufradāt, and build grammatical understanding through the naḥw and ṣarf sciences inductively and contextually.